Hubungan Pola Konsumsi Monosodium Glutamate (MSG) dengan Hipertensi - Nur Nisa Suryani Mangopa; Wisudawan Wisudawan; Nurhikmawati Nurhikmawati (Pusat riset dan Inovasi Nasional, 2025)
Hypertension, a major risk factor for cardiovascular disease, continues to show increasing prevalence, including in young people. One factor that potentially influences blood pressure is the consumption of monosodium glutamate (MSG), which is often used as a food additive to enhance flavor. Although MSG has long been used in various dishes, recent research suggests that MSG consumption may affect blood pressure through several mechanisms. This study aims to analyze the relationship between MSG consumption patterns and the incidence of hypertension using a narrative review approach. In this study, various scientific journals from 2016 to 2025 that discuss the impact of MSG on blood pressure were analyzed. The analysis results indicate that high and long-term MSG consumption can contribute to increased systolic and diastolic blood pressure. This can occur both directly through increased sodium intake hidden in MSG and indirectly through inflammatory pathways, oxidative stress, metabolic disorders, and changes in the gut microbiota. Several studies have also linked MSG consumption to obesity, which in turn can increase the risk of hypertension. Therefore, uncontrolled MSG consumption may serve as an independent risk factor for hypertension, especially in individuals with cardiovascular susceptibility. In conclusion, it is important to raise public awareness, regulate, and monitor MSG consumption to prevent negative impacts on public health, particularly in clinical practice and public health policy. The increasing prevalence of hypertension, which is increasingly found in young people, is a global health problem that requires serious attention. One factor that is no less important in the development of hypertension is the consumption of food additives, such as monosodium glutamate (MSG).